For love or money - Keene, Carolyn (New York : Pocket Books, 1995)
When the fiance of one of the richest and most respected citizens of River Heights is threatened with death, Nancy is called in to investigate the likely suspects, among whom are all of his heirs.
Primary
Keywords: Mystery and detective stories; Inheritance and succession -- Fiction; Mystery fiction; Young adult fiction; Drew, Nancy (Fictitious character) -- Fiction; Inheritance and succession -- Fiction